Hemodynamic features of adaptation to physical loads in female athletes of different age groups - Apokin, V. V.; Povzun, A. A.; Povzun, V. D. (Theory and Practice of Physical Culture, 2019)
The article is devoted to the analysis of the types of cardiovascular response to physical loads among female athletes of different ages and skill levels in terms of the zone time offset.